THE EFFECT OF TOPIC ON RATE OF SPEECH - García-Amaya, Lorenzo (ELIA: Estudios de Lingüística Inglesa Aplicada, 2017)
Abstract This study reports on the influence of a given topic on rate of speech, one measure of oral fluency. Twenty college-level learners of Spanish from four learner populations participated in a thirty-minute interview. The four groups were classified as follows: fifth semester with no experience abroad (AH1), seventh semester with no experience abroad (AH2), seventh semester with one or two semesters abroad (SA), and first year students with experience in an intensive overseas immersion program (IM). A total of twelve common topics were found to appear within the course of each interview. A quantitative analysis followed, and an overall mean rate of speech was calculated for each topic across all participants’ interviews. A Mixed Model was run to determine if significant differences occurred between topics and groups. Results showed that averaging among groups, there was a significant difference in the response according to topic as well as a significant interaction between Group and Topic, indicating that differences between groups depended on the topic discussed. Implications are drawn for future work on fluency measures, given the findings of the current analysis. Resumen Los resultados del presente estudio muestran la influencia de un determinado tema en una medida de fluidez, la velocidad de habla. Un total de veinte aprendices de español de cuatro grupos distintos participaron en una entrevista de 30 minutos. Durante la recolección de datos todos los participantes estaban matriculados en una universidad pública de los EEUU. Los cuatro grupos eran: quinto semestre sin experiencia en el extranjero (AH1), séptimo semestre sin experiencia en el extranjero (AH2), séptimo semestre con uno ó dos semestres de experiencia en el extranjero (SA), y estudiantes de primer año con experiencia en un programa de inmersión en el extranjero de carácter intensivo (IM). Durante el análisis de cada entrevista se encontró un total de doce temas comunes para todos los participantes. Se prosiguió con un análisis cuantitativo y se calculó una media total de velocidad de habla para cada tema a lo largo de las veinte entrevistas. Con el propósito de encontrar cualquier diferencia significativa entre los temas y los grupos de participantes se aplicó un modelo mixto, que reveló que había una diferencia significativa en la respuesta entre los temas así como una interacción entre grupo y tema, lo que significa que la cantidad de diferencias entre los grupos depende del tema discutido. Dados estos hallazgos, se plantean implicaciones para las investigaciones futuras en medidas de fluidez.